Plasticized Biodegradable Poly(lactic acid) Based Composites Containing Cellulose in Micro- and Nanosize - Katalin Halász; Levente Csóka (Journal of Engineering)
The aim of this work was to study the characteristics of thermal processed poly(lactic acid) composites. Poly(ethylene glycol) (PEG400), microcrystalline cellulose (MCC), and ultrasound-treated microcrystalline cellulose (USMCC) were used in 1, 3, and 5 weight percents to modify the attributes of PLA matrix. The composite films were produced by twin screw extrusion followed by film extrusion. The manufactured PLA-based films were characterized by tensile testing, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), wide angle X-ray diffraction (WAXD), and degradation test.